Environmental Politics: Domestic and Global Dimensions by Jacqueline Vaughn Switzer, 3rd edition, Boston, New York: Bedford/St. Martin's, 2001, 336 pp. (American Journal of Islam and Society, 2001)
The problem that confronts scholars who intend to engage in organizing issuesassociated with the environment in a manner that is logical and coherent is thatmany of those issues are conceptually overlapping, territorially interrelated, andacademically multidisciplinary. Added to this are the submerged and not so submergedtensions between environmentalism on the one hand, which restrains thefrontier exercise of human power and control over natural resources, and neoliberali.smon the other, which ordinarily considers such limitations oddities. Manyof the scholars who have been successful in this endeavor have tried to focus onrelated environmental mediums, issues, or regions.Despite its wider scope, Environmental Politics: Domestic and Global Dimensions,which is in its third edition, weaves through the maze of topics it covers using aprocess perspective. The book focuses on formal and informal institutions andprocesses in trying to develop an understanding about how global environmentalpolicies are developed in the United States. It is essential to note from the outsetthat the domestic and global dimensions of the book basically focus on the UnitedStates' responses to those challenges and, accordingly, a foreign reader may readinto the title: The US. Environmental Politicr: Domestic and Global Dimensions.The author, Dr. Jacqueline V. Switzer, does not waste any time in letting thereader know that the approach to the book is through the process model, a processwhereby the Congress, the president and his executive branch, and the judiciaryjostle for influence in formulating, implementing or redirecting environmentalpolicies (p. viii). An associate professor of political science at Northern ArizonaUniversity, the author deploys her understanding of the history, process, and conflictinginterests that have shaped the United States' environmental policies bothat home and at the international plane, to organize the complex issues covered inthe book. The third edition is remarkable for carefully updating a book that isreputed to be an information powerhouse regarding environmental policy, actors,disputes, and processes, up through the final years of the Clinton administration.It also incorporates, in each chapter, a global dimension of the main topic of thechapter, and it revises the "Another View, Another Voice" boxes of each chapter ...